PBL-Based e-LKPD (Problem Based Learning) to Facilitate Student Concept Understanding on Human Sense System Materials (Journal of Biology Education, 2022)
The use of technology today is very useful for online learning, namely as a provider of various learning resources. LKPD (Student Worksheet) is one of the learning resources that can be used by students in learning. E-LKPD based on PBL ( Problem Based Learning ) can be applied in biology learning on the material of the human sense system in which there are practicum activities. The purpose of this study was to produce a PBL-based e-LKPD, to test the feasibility and practicality as well as the effectiveness of the media in facilitating the ability to understand concepts and independent learning of students. The development model in this study uses the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) . The feasibility test is carried out by experts and the e-LKPD readability test. The potential of e-LKPD in facilitating students' conceptual understanding skills is obtained from the results of student work and posttest results. The results showed that the feasibility level of e-LKPD according to media and material experts was 71.15% (adequate) and 85.57% (very feasible). The readability of e-LKPD according to students is 80.12% (adequate). The results of student work in working on e-LKPD showed a good category with a percentage of 80.31% (XI MIPA 4) and 82.83% (XI MIPA 6). And the average posttest results for both classes get a percentage of 94.11% and 91.17% . The conclusion of this study is that the PBL-Based e-LKPD that has been developed is feasible and effective to use in learning.